IN VITRO CYTOTOXICITY ASSAY OF Petrosia sp. ETHANOL EXTRACT BY USING MTT METHOD OF T47D BREAST CANCER CELL LINE - Asniar Pascayantri; Mini Bekti Ningsih; Baru Sadarun; Muhammad Hajrul Malaka; Adryan Fristiohady; Fadhliyah Malik; Sahidin I (Universitas Muhammadiyah Magelang, 2022)
Breast cancer is increasing as the constraints of side effects, drug-resistant, and high medical costs. Indonesia has a variety of marine biotas that can be explored. The sponge is one of the marines biotas that had potential candidates for anticancer compounds. The secondary metabolites of sponge such as steroids, alkaloids, polyketides, terpenoids, and polyacetylenes have pharmacology effects as anti-inflammation, antineoplastic and cytotoxic activity. The study is aimed to determine the secondary metabolite of Petrosian sp. ethanol extract and the cytotoxic activity at the T47D cell line of breast cancer. The ethanol extract of Petrosian sp. is obtained by maceration using 96% ethanol as a solvent. Extract weight is obtained 274.7 grams with a 2.94% yield of values. Cytotoxicity assay was using MTT methods with IC50 parameters by using software GraphPad prism version 5. Secondary metabolites of Petrosian sp. ethanol extract showing alkaloids, flavonoids, steroids, tannins, and saponins. The possible compound that showed anticancer activity is spinasterol. Cytotoxicity activities of Petrosian sp. ethanol extracts showing IC50 values at 78.13 ppm and IC50 values at 65.88 ppm on positive control. These results proved cytotoxicity activities had moderate cytotoxicity.